Desempenho do Piauçu (Leporinus macrocephalus) Arraçoado com Dietas Contendo Diferentes Teores de Tanino - Quintero Pinto, Luis Gabriel; Pezzato, Luiz Edivaldo [UNESP]; De Miranda, Edma Carvalho; Barros, Margarida Maria [UNESP] (My University, 2001)
This experiment was undertaken to evaluate the effect of dietary tannin on growth performance and carcass composition of piauçu, for sixty days. Twenty one aquaria (80 L) were supplied with dechlorinated tap-water (1 L/min) in a closed system. Water quality was controled by biologic filter and heater. Fish, with inicial average weight 5.06 g, in a triplicate aquaria, were randomly assigned to each of 7 treatments. Experimental diets were formulated to contain approximately 3,200 kcal of digestible energy, 30% crude protein and 0.0, 0.23, 0.46, 0.69, 0.92, 1.37 and 1.82% of total tannin. Although 0.69% of tannin added did not affected apparent feed conversion and protein efficiency ratio, concentrations equal or higher than 0.46% resulted lower weight gain. Piauçu was sensitive to condensed tannin which had significant harmful effect on metabolism and biological value of dietary nutrients.
Growth Performance of Piauçu (Leporinus macrocephalus) Fed Diets with Different Levels of Tannin
Keywords: Barbatimão; Growth performance; Leporinus macrocephalus; Piauçu; Tannin